1969
DOI: 10.1007/bf01787351
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics in the American tropics. IV. Temporal changes effected in natural populations ofDrosophila melanogaster from Colombia

Abstract: Samples of Drosophila melanogasler were taken eactl month over several years from a locality in Fusagasug~, Colombia. Temporal shifts in gene frequencies were found. These reflect important adaptive changes in the populations, and the kind of gene pool modifications that are necessary for the better occupation of local temporal niches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In time the give-and-take of genes switching between the molecular parasite and those of the host had to gradually respond to a selection process, while allowing for a certain reduction of fitness. Even between drastic genes of the genetic load, different alleles that guide to the same adaptive response (similar to the ping-pong game we just referred to) have been repeatedly found, through the analysis of population genetics of wild strains of Drosophila melanogaster, to have adaptive features (survival) resulting from a switching between those genes that permit semi-lethality and sub-vitality without causing mortality to those that caused near-normal viability (Hoenigsberg and Navas, 1965;Hoenigsberg et al, 1968Hoenigsberg et al, , 1969aHoenigsberg et al, ,b, 1973.…”
Section: Introductionmentioning
confidence: 96%
“…In time the give-and-take of genes switching between the molecular parasite and those of the host had to gradually respond to a selection process, while allowing for a certain reduction of fitness. Even between drastic genes of the genetic load, different alleles that guide to the same adaptive response (similar to the ping-pong game we just referred to) have been repeatedly found, through the analysis of population genetics of wild strains of Drosophila melanogaster, to have adaptive features (survival) resulting from a switching between those genes that permit semi-lethality and sub-vitality without causing mortality to those that caused near-normal viability (Hoenigsberg and Navas, 1965;Hoenigsberg et al, 1968Hoenigsberg et al, , 1969aHoenigsberg et al, ,b, 1973.…”
Section: Introductionmentioning
confidence: 96%
“…March 1976 weather factors; positively with summer rainfall and negatively with the average daily temperature range of the week prior to collection. Hoenigsberg et al (1969Hoenigsberg et al ( , 1973 observed a niche-dependent change of lethal genes in the American tropics. The periodic use of pesticides was considered as a major cause.…”
mentioning
confidence: 99%